2016
DOI: 10.3847/0004-637x/818/2/123
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Explosions in Axisymmetric Ab Initio Core-Collapse Supernova Simulations of 12–25 Stars

Abstract: We present four ab initio axisymmetric core-collapse supernova simulations initiated from 12, 15, 20, and 25 M  zero-age main sequence progenitors. All of the simulations yield explosions and havebeen evolved for at least 1.2 s after core bounce and 1 s after material first becomes unbound. These simulations were computed with our CHIMERA code employing RbR spectral neutrino transport, special and general relativistic transport effects, and state-of-the-art neutrino interactions. Continuing the evolution bey… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
300
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(316 citation statements)
references
References 188 publications
(291 reference statements)
12
300
4
Order By: Relevance
“…Since the neutrino power deposition goes approximately as the product of this depth and the luminosities, high-compactness progenitors have an advantage. Therefore, it is feasible that more massive models might be more explosive, and this trend has been seen by other modelers (Summa et al , 2018Bruenn et al 2016). In fact, in the Summa et al and Bruenn et al papers for the Woosley and Heger (2007) models, the postbounce explosion times increase in the sequence 20, 25, 15, and 12 M , which is clearly not monotonic with compactness.…”
Section: Compactnessmentioning
confidence: 94%
See 2 more Smart Citations
“…Since the neutrino power deposition goes approximately as the product of this depth and the luminosities, high-compactness progenitors have an advantage. Therefore, it is feasible that more massive models might be more explosive, and this trend has been seen by other modelers (Summa et al , 2018Bruenn et al 2016). In fact, in the Summa et al and Bruenn et al papers for the Woosley and Heger (2007) models, the postbounce explosion times increase in the sequence 20, 25, 15, and 12 M , which is clearly not monotonic with compactness.…”
Section: Compactnessmentioning
confidence: 94%
“…To the point, Skinner et al (2016) have shown that the ray-by-ray anomalies in the angular distribution of the radiation field and corresponding neutrino heating rates can reinforce the axial sloshing motions in 2D and push the shock into explosion. 1 Bruenn et al (2013Bruenn et al ( , 2016 find explosions in 2D (axially symmetry) for all the progenitors they studied (the 12-, 15-, 20-, and 25-M models of Woosley and Heger 2007), but the models all explode at about the same post-bounce time (∼100 milliseconds) and the shock radii never decrease in value. When performed in 3D for the 15-M model of Woosley and Heger (2007), Lentz et al (2015) obtain a weaker explosion delayed in its onset by an extra ∼100 milliseconds.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Detailed spherically symmetric one-dimensional (1D) simulations do not explode (Liebendörfer et al 2001), except when particular low-mass progenitor models are used (e.g., Fischer et al 2010;Hüdepohl et al 2010). Multiple simulations including energydependent (multi-group) neutrino transport and imposing axial symmetry (2D) do exhibit explosions (Müller et al 2012b(Müller et al , 2012aBruenn et al 2013Bruenn et al , 2016, although some do not . Interestingly, the first simulations including ray-by-ray neutrino transport 11 without symmetries imposed three-dimensionally on the hydrodynamics did not find explosions in models that exploded when axisymmetry was assumed (Hanke et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The delayed neutrino mechanism (e.g., Bruenn et al 2016;Janka et al 2016;Müller 2016;Burrows et al 2017), although the most popular in the literature, encounters problems (e.g., Papish et al 2015;Kushnir 2015b). An alternative mechanism to account for all CCSNe is the jet feedback mechanism (JFM; for a review see .…”
Section: Introductionmentioning
confidence: 99%